Analysis of crack-tip plastic zone in a Compact Tensile Shear (CTS) Specimen - Shashidhar K. Kudari; C. M. Sharanaprabhu (Fracture and Structural Integrity)
The minimum plastic zone radius (MPZR) criterion is one of the recent criterions to estimate crack initiation direction under mixed mode loading. The MPZR theory is based on the theoretical computations of plastic zone size (PZS). In this investigation, the shape and size of crack-tip plastic zones have been estimated by analytical and the elastic finite element computations in a Compact Tensile Shear (CTS) specimen under mixed mode (I/II) loading according to von Mises yield criteria. The theoretical and the finite element analysis results are compared to analyze the minimum plastic zone radius (MPZR) criterion for crack-initiation angle with reference to the loading angle and stress intensity factor.